The Legal Effects of the Public Works Contract in Iraq - Abood Awad, Farkad (International Journal of Psychosocial Rehabilitation, 2020)
The public works contract is one of the important administrative contracts concluded by the administration in order to satisfy the public needs. This need has emerged largely in Iraq after 2003 due to the circumstances of the international war, through the circumstances of the internal war and terrorism experienced by the naked. As a result, there was an urgent need to establish or rebuild the infrastructure on which the Iraqi state is based, including buildings, roads, bridges and related cleaning, sweeping, spraying, dyeing and other works. However, the implementation of the public works contract in Iraq has not fully had legal implications in terms of the quality of the service provided to the public to satisfy their needs, in addition to the frequent theft of contractors and the failure to carry out the work. This is due to our modest assessment of the laxity and fragility of the forms of administrative contracts concluded between the administration and the contractor or to the negligence of the administration and its disregard for the control of the proper execution of contracts or the conclusion of fictitious administrative contracts as a result of the administrative corruption that is rampant in its joints. Therefore, we decided to look into the challenges facing this administrative contract in Iraq, while demonstrating the effectiveness of its legal implications in terms of providing public service to the public and providing treatment as much as possible.